Environmental Performance of ASEAN Countries: Sustainability Accounting Perspective - Andi Nurrahma Gaffar; Sri Sundari ; Mediaty (Journal of Accounting, Economics, and Business Education, 2026)
This study analyzes the environmental and natural resource performance of ASEAN countries from a sustainability accounting perspective using ASEAN Key Figures 2025. It applies a descriptive quantitative approach based on secondary data and comparative descriptive analysis. The study focuses on transportation, energy, agriculture, and forestry indicators. The findings show that ASEAN countries demonstrate varied sustainability performance. Transportation infrastructure and mobility have expanded, but may increase environmental pressure. Electricity access has improved in most countries, yet clean fuel use and renewable energy adoption remain uneven. Agricultural production is relatively stable but concentrated in several major countries. Forestry indicators show differences in forest cover and biodiversity conservation. The study concludes that official environmental and natural resource indicators can be interpreted as macro-level sustainability accounting information because they reflect accountability for sustainable development across ASEAN countries.